Agronomic and environmental benefits of ‘re-using’ a biodegradable mulching film for two consecutive lettuce cycles - Di Mola, Ida; Cozzolino, Eugenio; Ottaiano, Lucia; Riccardi, Riccardo; Spigno, Patrizia; Fagnano, Massimo; Mori, Mauro (Italian Journal of Agronomy, 2022)
Biodegradable films are a valuable and sustainable alternative to plastic films for mulching soils since they avoid the environmental and economic problems related to plastic removal and disposal. Nevertheless, the fast degradation of such materials could make them unsuitable for mid- to long-term use. In a field experiment, the agronomic performance of a biodegradable mulching film (MB) was compared to that of conventional low-density polyethylene (LDPE) film for two consecutive lettuce cycles (winter and spring). In the conditions of this trial, MB showed good resistance to atmospheric agents, with a reduction of its integrity and mechanical properties only after six months. The effects on soil temperature and lettuce yield did not differ from those obtained with LDPE films. The effect on harvest timing was the same as that with LDPE in the spring cycle, while in the winter cycle, the harvest was delayed by about five days compared to LDPE. Mulching films reduced nitrate accumulation in leaves mainly during the winter cycle. However, the effect needs to be further explored with experiments in different pedoclimatic conditions that consider the effects of mulching on nitrification and nitrate-reductase activity that could be affected by changes in soil temperature and moisture. Highlights - Biodegradable mulching films (MB) showed good mechanical resistance in the medium-long term (2 consecutive lettuce cycles). - Decrease in integrity and resistance to tearing became significant after 150-170 days. - The effect of MB on lettuce yield quantity and quality was comparable with that using low-density polyethylene (LDPE) films. - The effects of both mulching films on leaf nitrate content need further research in different pedoclimatic conditions. - MB can be recommended since it reduces the economic and environmental costs of removal and disposal of LDPE films.